The effect of whitening toothpastes on colour change and surface roughness of restorative materials = El efecto de las pastas dentales blanqueadoras en el cambio de color y la rugosidad de la superficie de los materiales de restauración - Dayı, Burak
To examine the colour change and surface roughness of giomer, microhybrid composite and nanohybrid composite after brushing with whitening toothpastes. Disc-shaped samples of giomer, microhybrid composite and nanohybrid composite were divided into three subgroups(n=10), with the initial colour measured with a spectrophotometer and the surface roughness measured with a mechanical profilometer. The samples, which were immersed in coffee solution were brushed once a day with whitening toothpastes (Opalescence Cool Mint (OCM), Colgate Optic White Extra Power (COW) and Signal White Now Gold (SWN)) for 12 days. Colour change and surface roughness were measured again after the colouring-brushing cycle. All of the analyses were performed using appropriate statistical hypothesis tests. The highest increase in surface roughness was seen in the microhybrid composite group applied with SWN (p<0.05). The group with the least increase was the giomer group applied with SWN (p<0.05). While the least colour change was observed in the COW applied nanohybrid composite group (ΔE00=1,814), the most colour change occurred in the COW applied giomer group (ΔE00=5.943). After the use of whitening toothpastes, the roughness of giomer, microhybrid composite and nanohybrid composite surfaces was increased and a colour change above the clinically accepted value was observed.